Interaction of Body Mass Index on the Association Between N‐Terminal‐Pro‐b‐Type Natriuretic Peptide and Morbidity and Mortality in Patients With Acute Heart Failure: Findings From ASCEND‐HF (Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure). Issue 3 (3rd February 2018) - Bhatt, Ankeet S.; Cooper, Lauren B.; Ambrosy, Andrew P.; Clare, Robert M.; Coles, Adrian; Joyce, Emer; Krishnamoorthy, Arun; Butler, Javed; Felker, G. Michael; Ezekowitz, Justin A.; Armstrong, Paul W.; Hernandez, Adrian F.; et al.
Abstract : Background: Higher body mass index (BMI) is associated with lower circulating levels of N‐terminal‐pro‐b‐type natriuretic peptide (NT‐proBNP). The Interaction between BMI and NT‐proBNP with respect to clinical outcomes is not well characterized in patients with acute heart failure. Methods and Results: A total of 686 patients from the biomarker substudy of the ASCEND‐HF (Acute Study of Clinical Effectiveness of Nesiritide in Decompensated HF ) clinical trial with documented NT‐proBNP levels at baseline were included in the present analysis. Patients were classified by the World Health Organization obesity classification (nonobese: BMI <30 kg/m 2, Class I obesity: BMI 30–34.9 kg/m 2, Class II obesity BMI 35–39.9 kg/m 2, and Class III obesity BMI ≥40 kg/m 2 ). We assessed baseline characteristics and 30‐ and 180‐day outcomes by BMI class and explored the interaction between BMI and NT‐proBNP for these outcomes. Study participants had a median age of 67 years (55, 78) and 71% were female. NT‐proBNP levels were inversely correlated with BMI ( P <0.001). Higher NT‐proBNP levels were associated with higher 180‐day mortality (adjusted hazard ratio for each doubling of NT‐proBNP, 1.40; 95% confidence interval, 1.16, 1.71; P <0.001), but not 30‐day outcomes. The effect of NT‐proBNP on 180‐day death was not modified by BMI class (interaction P =0.24). Conclusions: The prognostic value of NT‐proBNP was not modified by BMI in this acute heart failure population. NT‐proBNP remains a useful prognostic indicator of long‐term mortality in acute heart failure even in the obese patient. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00475852.